Efecto del porcentaje de cobalto y temperatura de recocido en películas delgadas semiconductoras de óxido de níquel sobre el tamaño de los cristales y la conductividad eléctrica utilizando la técnica drx y el método de cuatro puntas. - Vasquez Arribasplata, Felipe Gonzalo (2018)
In this investigation thin films of NiO doped with cobalt of 90 nm of thickness have been prepared, these were deposited by spinning coating on borosilicate glass substrates of 12mm x 12 mm x 1mm, through the sol-gel method, the same ones that are evaluated the effect of the molar percentage (3, 5 and 7%) of dopant and the annealing temperature of (250,300 and 350 ° C) that influencing the electrical, optical properties and in the same way there being a relationship with the crystalline structure. X-ray diffraction measurements (u.a) and intensity patterns of the UV-Vis absorption bands (u.a) show that with the method used thin films of NiO have an FCC structure (figures 3.8 - 3.10), As the annealing temperature increases, its crystal sizes increase, however the cobalt dopant decreases it, the size details and network parameters in each temperature and percentage (table 3.2). The percentage of Co and in the annealing temperature increase the bandwidth forbidden (Eg) are decreased, obtained in 3.26 eV the lowest value of this investigation and displace the exciton peak towards higher energies, evidencing a regime of quantum confinement. The resistivity and electrical conductivity of the films show that while the amount of dopant and the annealing temperature increase the electrical resistivity decreases while the electrical conductivity increases. Obtaining at 350 ° c and 7% doped 8.19 x 10-6 Ω -1 cm-1, this being the highest conductivity value obtained.